(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The current research aims to study is to reveal the ways of working textual exchange and what occurs from the visual illusion within the linear painting, such as research procedures, which included his community on linear panels embodied in which the exchange of visual text within it, has included most types of lines almost reached the number of community (30) panel has selected the researcher (3) models, a percentage representing (10%) of the original community and intentionally, according to what the researcher followed in his analysis on the descriptive approach (content analysis) adopting the analysis tool represented The analysis form, which included main and sub-paragraphs represented the pillars adopted in the analysis of his samples and designed according to the information outcome and the indicators that came out of the research trends, it was presented to a group of specialized experts to modify its paragraphs and indicate their suitability to the subject of the research and the researchers reached several results, including: The calligraphic painting varied on mutual formative bases by achieving aesthetic values based on the Innovation, and following the manifestations of exchange enabled the calligrapher to disassemble, reconvert and reconstruct the elements of the painting into a new concept and content. In addition, calligraphers resort to exchange in the text for a necessity imposed by meaning first, and to show skill second. The researchers also recommended a set of recommendations and proposals, including: Strengthening the link between research centers and academic researchers to investigate knowledge and benefit from it in developing contemporary linear formations according to the visions of the concept of visual text interchangeability to enhance aesthetic values in linear painting.